2018
DOI: 10.1371/journal.pone.0191861
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the behaviour of water in glycerol solutions by using delayed luminescence

Abstract: The crucial role of water in the engine of life have encouraged many researchers in studying, both theoretically and experimentally, the possible “structure” of water. Many properties of water have been related to the interplay between two distinct and interconverting structural species, namely the low-density water (LDW) and the high-density water (HDW). Supported by the results obtained with other aqueous solutions, this paper deals with the possibility of using the ultra-weak delayed luminescence (DL) to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…DL seems to be closely correlated with the functional status of different biological systems studied to date [11][12][13][14][15][16] . Moreover it has been also possible to reveal structures inside liquid solutions of biological interest [17][18][19][20][21] . Although the precise origin of the DL is still a subject of debate [22][23][24][25][26][27] , these evidences suggest it may vary depending on the REDOX state of the biological system analyzed and according to its degree of homeostatic stress [27] .…”
Section: Introductionmentioning
confidence: 99%
“…DL seems to be closely correlated with the functional status of different biological systems studied to date [11][12][13][14][15][16] . Moreover it has been also possible to reveal structures inside liquid solutions of biological interest [17][18][19][20][21] . Although the precise origin of the DL is still a subject of debate [22][23][24][25][26][27] , these evidences suggest it may vary depending on the REDOX state of the biological system analyzed and according to its degree of homeostatic stress [27] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to enhanced thermal motions at higher temperature, [51,72] higher fluctuations of water inside the glycerol cavities are accommodated [71] . The influence of temperature on the structural arrangement of glycerol‐water aggregates is proven to be negligible, [73,74] the previously described presence of water molecules in the glycerol voids can also be confirmed at RT.…”
Section: Resultsmentioning
confidence: 72%
“…The widespread use of such materials -chemically benign but physically strong -is an expanding technology in the pharmaceutical industry today. In fundamental research too, specialist spectroscopic techniques have revealed extended structuring in solutions of glycerol and derivatives (Grasso et al 2018).…”
Section: History Of the Mediummentioning
confidence: 99%